Books and Their Owners Based on Kassam Deftersof Sarajevo Court 1762–1787 (Prilozi za orijentalnu filologiju, 2017)
Based on the property lists (kassam defters) of the deceased inhabitants of the Sarajevo kadilik, the article presents books and their 472 owners for the period 1762–1787. After identifiying the limitations of the sources, the article presents book-owners according to their gender, religion, profession and title. Books are analyzed in terms of the size of book-collections, the most widespread and the most expensive books, printed books, and magazines. The list of works is given according to their number in these defters.